Application of shakedown theory in the structural design of bituminous pavements - Liu, Shu (2016)
Excessive rutting, one of the major distress modes of bituminous pavements, is mainly caused by the accumulation of load-induced permanent deformation. However, current pavement design approaches against the excessive rutting are mainly developed using the theory of elasticity. Recently, a new pavement design approach based on the shakedown concept has attracted lots of attention because it can consider plastic properties of pavement materials. However, most of the existing shakedown solutions were developed for pavement foundations composed of granular materials and soils. Very limited work has been reported on bituminous pavements. Besides, current studies usually assume homogeneous, isotropic pavement materials obeying an associated plastic flow rule (termed as standard materials in the present study), which may not be realistic for pavement materials.